Bidens pilosa chemoprotective effect on induced breast cancer in rats - Arroyo, Jorge (2010)
Introduction: Bidens pilosa species belonging to the Asteraceae family, known in Peru as love dry bur, is credited with anti-inflammatory, diuretic, hepatoprotective effects. Objectives: To determine the protective effect of phenolic compounds and flavonoids extracted from Bidens pilosa L whole plant on breast cancer induced in rats by 7,12-dimethylbenz (A) anthracene (DMBA). Design: Experimental. Setting: Laboratory of Pharmacology, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material: Bidens pilosa L whole plant collected in Santiago de Cao, Ascope, La Libertad, and female rats. Interventions: Phenolic compounds and flavonoids were obtained by rapid column chromatography with solvents of increasing polarity; by thin layer chromatography on a preparative scale four phenolic compounds were isolated and elucidated by UV-Visible spectroscopy with shift reagents. Breast tumors were induced with DMBA administered orally to four groups of rats: normal control group, group with toxic inductor (TI) of cancer, group with TI and ethanolic extract, and group with TI and methanol fraction in doses of 300 mg/kg. Main outcome measures: Induced breast cancer protection. Results: Development of mammary adenocarcinoma tends to slow with treatments, more with the methanol fraction; the oxidative stress marker decreased in the groups treated with the plant, better with the methanol fraction; there were fewer micronuclei (genotoxicity) in animals receiving treatment. Conclusions: Under experimental conditions both Bidens pilosa methanol extracts and fractions halted induced breast cancer progression in rats.